Health belief and Dengue hemorrhagic fever preventive behaviors among population of Pak-Nam sub-district, Bang-Kla district, Chachoengsao province - คำสี ศิรินันท์ (Journal of Medicine and Health Sciences, 2018)
The objective of this study was to investigate the association between health belief and health behavior for Dengue hemorrhage fever prevention in population at PakNam municipality, Bang-Kha district, Chachoengsao province, Thailand, which focused on the perception of susceptibility, perception of disease severity and behavior for Dengue hemorrhage fever prevention. The study was descriptive research by cross-sectional study using multi-stage sampling. Sample size was designed using the Krejcie and Morgan tables which was 140 persons. The instrument used to collect data was a questionnaire. The data was demonstrated as percentage, mean, standard deviation and Pearson product-moment correlation. The results showed that the perception of susceptibility was 2.37±0.25 (mean±SD), there was no statistically significant association with Dengue prevention behavior (r=0.032; p-value=0.703), whereas the perception of disease severity was 2.33±0.30 (mean±SD), which showed significant correlation with Dengue fever prevention behavior (r=-0.209; p-value=0.013).